Effect of partial substitution of diesel fuel by natural gas on performance parameters of a four-cylinder diesel engine - Saidur, Rahman; Jahirul, M.I.; Moutushi, T.Z.; Imtiaz, H.; Masjuki, Haji Hassan (SAGE Publications, 2007)
This work presents the evaluation of some performance parameters with cost comparison for a four-cylinder diesel engine under a variety of operating conditions, before and after converting to dual fuel engine. The experiment used a converted dual fuel diesel engine which can run on a hybrid mixture of diesel and natural gas (NG). The focus of this study is on the engine thermal efficiency, exhaust gas temperature, lubricating oil temperature, air fuel ratio, specific fuel cost, and specific fuel consumption under different operating conditions. A comparison of the cost economy of pure diesel engine and gradually converted dual fuel engine is also performed. Performance parameters with engine power (kW) are compared as well. This study concludes that fuel cost can be reduced significantly by substituting diesel with NG. Few costly accessories are needed for converting stationary diesel engine into dual fuel engine without altering basic engine components. Other findings from this study include relation between brake thermal efficiency, brake specific fuel consumption, and other performance parameters of engine.